PROGAM WALI ASUH DALAM MENINGKATKAN KUALITAS KONTROL DIRI SANTRI DI PONDOK PESANTREN - Fitriyah, Lailatul; mas'ula, wahibatul (JURNAL ISLAM NUSANTARA, 2021)
This study presents self-control of Islamic boarding school students who experience a changing cycle starting from small behaviors such as emotions, ghasab, stealing, and even violent behavior and bullying. Foster guardians here become the foundation or role model for students in Islamic boarding schools to control or control themselves so as not to commit a violation (violation) that has become a tradition or habit of students who must exceed the limit. The research method used is a qualitative case study type. This study indicates that the relevance of foster care can be a medicine for students against deviant behavior in Islamic boarding schools. Islamic boarding school students can control themselves from anything, through the Ruhul jihad program is a lecture/motivation, sharing stories/complaints, self-muhasabah is self-introspection, spiritual education is religious education/science. The existence of this program can positively impact both physically and spiritually to take ibroh and understand the regulation of the meaning of pesantren by its provisions so that this will create students who have faith, high-quality souls and are beneficial to society.